Performance characteristics of refrigeration cycle with parallel compression economization - Sarkar J. (My University, 2025)
Thermodynamic analyses and economizer pressure optimizations of ammonia, propane and isobutane-based refrigeration cycles with parallel compression economization are presented in this article. Energetic and exergetic performance comparisons with transcritical CO2 cycle are presented as well. Results show that the optimum economizer mass fraction as well as COP improvement increase with increase in cycle temperature lift. The expression for optimum economizer pressure has been developed. Study shows that the performance improvements using parallel compression economization are strongly dependent on the refrigerant properties as well as the operating conditions. Using parallel compression economization, carbon dioxide yields maximum COP improvement of 31.9% followed by propane (29.8%), isobutane (27.2%) and ammonia (11.3%) for studies ranges. In spite of higher COP improvement, the cooling COP as well as second low efficiency for carbon dioxide is still significantly lower than that for others. Component-wise irreversibility distributions show the similar trends for all refrigerants except CO2. Employing parallel compression economization in refrigeration cycle not only improves the cooling COP but also increase the compactness of evaporator. © 2010 John Wiley & Sons, Ltd.